Breeding and genetic aspects of creating productive forms of fast-developing spring bread wheat - B. V. Rigin; E. V. Zuev; V. A. Tyunin; E. R. Shreyder; Z. S. Pyzhenkova; I. I. Matvienko (Труды по прикладной ботанике, генетике и селекции)
Background. In Russia, wheat breeding should also focus on creation of earlier-maturing varieties with an optimal duration of the vegetation period reflecting territorial environmental features. It is very important to overcome the negative correlation between the early maturity and productivity of wheat. The present work was aimed at analyzing special features of genetic and physiological mechanisms of early maturity in spring wheat (Triticum aestivum L.) and at determining possibilities of creating recombinants with high development rate and plant productivity.Materials and methods. The study employed such ultra-early spring wheat accessions as 'Rico' (k-65588), 'Foton' (k-55696), 'Fori' lines (kk-65589 ... 65596) selected from F4 hybrids of 'Foton' x 'Rico', and 'Rifor' lines selected from F6-7 hybrids of 'Rico' x 'Forlani Roberto' (k-42641). Genetics of the development rate was studied using hybridological analysis and 'Triple Dirk' near isogenic lines. Photoperiodic sensitivity was evaluated under 18-hour (natural day) and at 12-hour (short day) conditions. Vernalization was performed within 30 days at 3°C.Results and conclusion. The ultra-early maturing accessions of spring wheat 'Rico', 'Foton', as well as 'Fori', 'Rifor 1', 'Rifor 6' and 'Rifor 7' lines had the shortest vegetation period in comparison with varieties from the VIR collection of plant genetic resources. These accessions had weak photoperiodic sensitivity and were insensitive to vernalization. The lines did not change their characteristics in different ecological conditions. Besides the Eps gene, Vrn-A1, Vrn-B1, Vrn-D1, Ppd-D1 and Ppd-B1 determined the rate of development of the ultra-early varieties 'Rico', 'Foton' and 'Fori'. Possibly, the Eps gene that controls ultra-earliness per se, is a set of polygenes (modifiers) with a low effect. No transgressive segregations in comparison with 'Rico' were recorded for the hybrids of the ultra-early 'Rico' with nine wheat varieties. A perspective cultivar 'Erythrospermum 25513' was created at the Chelyabinsk ARI with participation of 'Fori 7' line. 'Forlani Roberto' is a late variety, it responds to vernalization and photoperiod, and in good conditions its productive spike has 5-6 grains in the spikelet. The spring type of 'Forlani Roberto' is determined by the dominant gene Vrn-B1. The spikelet multi-seededness in productive 'Rifor' hybrids is determined by two or three genes and their expression depends on the environment. The selected ultra-early 'Rifor' lines have the number of grains per spike 1,5-2 times higher than in the parent line Rico, but the mass of grain per spike is below that of standard varieties. The yield per 1 m2 of Rifor 1, Rifor 8, Rifor 6 and Rifor 7 lines reached 81, 82, 84 and 94%, respectively, in comparison with the standard variety 'Leningradskaya 97'. Therefore, a possibility of creating wheat recombinants that combine ultra-earliness and high spike productivity is demonstrated.